2017
DOI: 10.1080/15384047.2017.1281499
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mutant KRAS and TP53 DNA in circulating exosomes from healthy individuals and patients with pancreatic cancer

Abstract: Pancreatic cancer presents with a dismal mortality rate and is in urgent need of methods for early detection with potential for timely intervention. All living cells, including cancer cells, generate exosomes. We previously discovered double stranded genomic DNA in exosomes derived from the circulation of pancreatic cancer patients, which enabled the detection of prevalent mutations associated with the disease. Here, we report a proof-of-concept study that demonstrates the potential clinical utility of circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(127 citation statements)
references
References 42 publications
3
115
2
1
Order By: Relevance
“…Both KRAS G12D and TP53 R273H mutations have been detected in exosomal DNA from patients with pancreas-associated pathologies, including pancreatic ductal adenocarcinoma, chronic pancreatitis and intraductal papillary mucinous neoplasm compared to healthy human subjects [145]. A combined isolation and analysis of exosomal RNA and cfDNA (together referred to as "exoNA") seems to improve blood-based liquid biopsy for EGFR mutation detection in NSCLC patients.…”
Section: Methods To Isolate and Identify Exosomesmentioning
confidence: 99%
“…Both KRAS G12D and TP53 R273H mutations have been detected in exosomal DNA from patients with pancreas-associated pathologies, including pancreatic ductal adenocarcinoma, chronic pancreatitis and intraductal papillary mucinous neoplasm compared to healthy human subjects [145]. A combined isolation and analysis of exosomal RNA and cfDNA (together referred to as "exoNA") seems to improve blood-based liquid biopsy for EGFR mutation detection in NSCLC patients.…”
Section: Methods To Isolate and Identify Exosomesmentioning
confidence: 99%
“…Pancreatic cancer is the third leading cause of cancer-related death in the United States with a median overall survival of less than one year and five-year survival of only 7.7% (1,2). At the time of diagnosis, most patients with pancreatic cancer have metastatic disease and are at a disease stage that is no longer curable (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Cell-free (cf-DNA) is one of the fastest-growing liquid biopsy biomarkers that has been extensively validated and is currently used routinely in the clinical setting to test for specific tumoral mutations in oncogene driven cancers [7][8][9][10][11] . A number of studies have also demonstrated the emerging role of extracellular vesicles (EV) as another complementary liquid biopsy source [12][13][14][15][16] . EV are bioactive vesicles secreted by all cell types, including vesicles of various sizes and biogenetic origin (e.g.…”
mentioning
confidence: 99%
“…exosomes, microvesicles, oncosomes and microparticles) and are implicated in carcinogenesis and in the facilitation of metastatic potential 12 . EV have also been found to contain molecular content reflective of the characteristics of the tumor and thus, EV and their contents have the potential to represent a novel liquid biopsy biomarker [12][13][14][15][16] . As EV are hypothesized to contain more intact molecular contents, EV-based liquid biopsy approaches provide an alternative to cell-free based approaches which rely on the detection of degraded, apoptotic cellular material 17 .…”
mentioning
confidence: 99%